Quality Enhancement of Internal Customers and Relationship with External Customers in Management Education: An Elucidate Study (Global Journal of Management and Business Research, 2018)
Success of any organization lies in the Quality of Service particularly in the Management Education Service. External Customers (Students) needs are given due priority accordingly internal customers (Teachers) are engaged in service with reference to their qualities. Quality should not be static but should be dynamic which undergo continuous improvement in the internal customers' capabilities which should bring positive result in the performance of external customers. Improvement in the Quality of internal customers is necessary in the development of the future human resources. This paper raise questions on the quality of internal customers and relationship with the quality of external customers. Primary data were collected from top 10 MESPO of Assam. The data were collected with the help of a set of two different questionnaires from 100 internal and 510 external customers of top 10 MESPO of Assam. Hypothesis established for the purpose of the study was tested with the help of both parametric and non parametric test of correlation.
Keywords: internal marketing; external marketing; internal customers; external customers management education services providing organizations